2020
DOI: 10.1016/j.applthermaleng.2019.114604
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and economic investigations of transcritical CO2-cycle systems with integrated radial-inflow turbine performance predictions

Abstract: Transcritical CO2 (TCO2) cycle systems have emerged as a promising power-generation technology in certain applications. In conventional TCO2-cycle system analyses reported in the literature, the turbine efficiency, which strongly determines the overall system performance, is generally assumed to be constant. This may lead to suboptimal designs and optimization results. In order to improve the accuracy and reliability of such system analyses and offer insight into how knowledge of these systems from earlier ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…In this investigation, the power capacity is fixed to 10 MW and the charge/discharge times are set to 6 h. The thermodynamic parameters of the PTES system are optimised using the optimisation method [71] to achieve the highest roundtrip efficiency considering the limitations of the working temperature of the storage materials and the manufacturing capability of the main components in practical applications. A sequential quadratic programming algorithm [72] has been proven to be the most reliable method for solving the optimisation problem.…”
Section: Assumption and Conditionsmentioning
confidence: 99%
“…In this investigation, the power capacity is fixed to 10 MW and the charge/discharge times are set to 6 h. The thermodynamic parameters of the PTES system are optimised using the optimisation method [71] to achieve the highest roundtrip efficiency considering the limitations of the working temperature of the storage materials and the manufacturing capability of the main components in practical applications. A sequential quadratic programming algorithm [72] has been proven to be the most reliable method for solving the optimisation problem.…”
Section: Assumption and Conditionsmentioning
confidence: 99%
“…Recently, operating conditions affecting turbine performance on Brayton cycles and CO 2 transcritical cycles have been investigated. 22,23 Hsieh 24 indicated the pseudocritical temperature of CO 2 in TRC should be increased to approach half the expander inlet temperature. Although CO 2 -based mixtures have been investigated in the literature, the associated system costs were markedly high because the supercritical pressure of CO 2 is higher than that of other organic mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Gayer et al 21 found that a pressure level of approximately 13.5 MPa maximized the thermal and exergetic efficiencies in a CO 2 transcritical cycle without a regenerator at a pressure range from 9 to 15 MPa. Recently, operating conditions affecting turbine performance on Brayton cycles and CO 2 transcritical cycles have been investigated 22,23 . Hsieh 24 indicated the pseudocritical temperature of CO 2 in TRC should be increased to approach half the expander inlet temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In future work, different geothermal temperature gradients can also be considered for different regions which have not been considered in this study. In addition, optimal designs and system performance with integrated component performance modelling [54] as well operational modelling in the presence of heat-source (or sink) intermittency while accounting for changing component performance are important in making predictions close to expectations in practice [55].…”
Section: Discussionmentioning
confidence: 99%